Formulación del Plan de Manejo Integral de Residuos Sólidos PMIRS en la Corporación Plaza Popular de la ciudad de Villavicencio - Vera Pérez, Luisa Fernanda (Universidad Antonio Nariño, 2023)
Nowadays it is of vital importance for every company to have an Integrated Solid Waste Management Plan. For this reason, the report contains a concise description of the formulation of a PMIRS carried out in the Plaza Popular Corporation in the city of Villavicencio, Department of Meta, in three phases according to the methodology described; In the first phase, an initial diagnosis was made through planning, a collection of primary and secondary information and finally a characterization that allowed us to determine the current condition and also by the quarting method, the amount and type of waste generated in a day in the market place was obtained. The second phase was given according to the results of the initial diagnosis and five programs related to solid waste were formulated in order to take advantage of them. In the third phase, a benefit/cost analysis of the programs was carried out in order to obtain the economic, social and environmental benefits of implementing a PMIRS in the Corporación Plaza Popular.